Reverse thinking: Taking a healthy diet perspective towards food systems transformations - Brouwer, Inge D.; Liere, Marti J. van; de Brauw, Alan; Domínguez-Salas, Paula; Herforth, A.; Kennedy, G.; Lachat, Carl; Omosa, Esther B.; Talsma, Elise F.; Vandevijvere, S.; Fanzo, J.; Ruel, Marie T. (Springer, 2021)
Food systems that deliver healthy diets without exceeding the planet’s resources are essential to achieve the worlds’ ambitious development goals. Healthy diets need to be safe, accessible, and affordable for all, including for disadvantaged and nutritionally vulnerable groups such as of smallholder producers, traders, and consumers in low- and middle-income countries. Globally, food systems are experiencing rapid and drastic changes and are failing to fulfil these multiple duties simultaneously. The international community therefore calls for rigorous food systems transformations and policy solutions to support the achievement of healthy diets for all. Most strategies, however, are essentially supply- and market-oriented. Incorporation of a healthy diet perspective in food system transformation is essential to enable food systems to deliver not only on supplying nutritious foods but also on ensuring that consumers have access can afford and desire healthy, sustainable, and culturally acceptable diets. This paper argues that this should be guided by information on diets, dietary trends, consumer motives, and food environment characteristics. Transformational approaches and policies should also take into account the stage of food system development requiring different strategies to ensure healthier diets for consumers. We review current knowledge on drivers of consumer choices at the individual and food environment level with special emphasis on low- and middle income countries, discuss the converging and conflicting objectives that exist among multiple food-system actors, and argue that failure to strengthen synergies and resolve trade-offs may lead to missed opportunities and benefits, or negative unintended consequences in food system outcomes. The paper proposes a menu of promising consumer- and food-environment- oriented policy options to include in the food systems transformation agenda in order to shift LMIC consumer demand towards healthier diets in low- and middle income countries.